2018
DOI: 10.1080/21582041.2018.1457170
|View full text |Cite
|
Sign up to set email alerts
|

Human capital, knowledge creation, knowledge diffusion, institutions and economic incentives: South Korea versus Africa

Abstract: This article compares African countries to South Korea in terms of knowledge economy (KE).Emphasis is laid on human capital, knowledge creation, knowledge diffusion, institutions and economic incentives. The analytical approach consists of providing knowledge economy catch-up strategies that can be understood within the context of country-specific gaps between the frontier country in KE and laggard African countries. The empirical evidence is based on sigma convergence with data for the period 1996-2010. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Government quality, the empowerment of women, and a large number of other indicators can be used for this purpose. The importance of considering human capital is supported by recent international literature regarding development, including the work of Guisan and Neira (2006), Guisan (2009Guisan ( , 2015, Asongu and Tchamyou (2018), Asongu 2017b), and Tchamyou (2017Tchamyou ( , 2018.…”
Section: Resultsmentioning
confidence: 99%
“…Government quality, the empowerment of women, and a large number of other indicators can be used for this purpose. The importance of considering human capital is supported by recent international literature regarding development, including the work of Guisan and Neira (2006), Guisan (2009Guisan ( , 2015, Asongu and Tchamyou (2018), Asongu 2017b), and Tchamyou (2017Tchamyou ( , 2018.…”
Section: Resultsmentioning
confidence: 99%
“…These findings, which are consistent with Meniago and Asongu (2018), can be partly explained by the relevance of primary education (compared to higher levels of education) in socio-economic development where economies are at early stages of industrialisation (Petrakis &Stamatakis, 2002;Asiedu, 2014;Asongu&Nwachukwu, 2018;Tchamyou et al, 2019b). Asongu and Tchamyou (2018) In another study on economic growth, Oluwatobi, Olurinola, Alege and Ogundipe (2018), investigated the knowledge capacity of Sub-Saharan Africa as well as its effect on economic growth. Using GMM on a panel of 32 countries over the period 1996-2012, they found that institutions and human capital weaken the relevance of innovation on economic growth.…”
Section: Building Knowledge Economies In Africamentioning
confidence: 70%
“…Semi-formal financial development (Propositions 2 and 6) is not used because of issues in degrees of freedom whereas non-formal financial development (Propositions 4 and 8) has a high degree of substitution with informal financial development. The mobile phone variable is the mobile phone penetration rate per 100 people (Tchamyou, 2017;Tchamyou & Asongu, 2019).…”
Section: Propositions and Testable Hypothesesmentioning
confidence: 99%